Improvement of sugarcane (Saccharum officinarum L. var. Isd. 39) using gamma irradiation and large scale plantlet production from M1 generation through in vitro culture - Akter, Shamima; Alam, N; Roy, PK (Jahangirnagar University Journal of Biological Sciences, 2016)
The present study was aimed to develop mutant sugarcane (Saccharum officinarum L. var. Isd. 39) using gamma radiation followed by regeneration of those mutants through in vitro technique. Five different doses of gamma radiation (10, 20, 30, 40 and 50 Gy) were applied to the sugarcane setts and among these doses 10 Gy irradiated mutant sugarcane showed the best agronomical traits. In addition, 10 Gy irradiated mutant sugarcane also contained higher sugar concentrations (14.25%) compared to control (14.23%). On the other hand, shoot tip and young folded leaf segments from the 10 Gy irradiated plants (M1 generation) were used as explants in in vitro culture. It was evident from the experiment that direct shoot regeneration was better than indirect regeneration. Young leaf segments produced the highest percentage (84%) of shoots when cultured on MS+1.0 mg/l Kin + 0.2 mg/l NAA. The mean number of shoots was recorded as 35 ± 1.12 in the same medium. Moreover, addition of 4% sucrose and 10% coconut water (CW) in the same medium increased the number of shoot up to 45 per culture. Best rooting was obtained from shoots cultured on half-strength of MS fortified with 1.0mg/l NAA and 0.5mg/l IBA. Well-rooted plantlets were transferred to poly bag containing soil and compost (2:1) for hardening. During hardening 70% plantlets survived, which were subsequently transferred to the experimental field. Jahangirnagar University J. Biol. Sci. 5(1): 1-9, 2016 (June)